2013
DOI: 10.1002/emmm.201201623
|View full text |Cite
|
Sign up to set email alerts
|

Reactive astrocytes promote the metastatic growth of breast cancer stem‐like cells by activating Notch signalling in brain

Abstract: Brain metastasis of breast cancer profoundly affects the cognitive and sensory functions as well as morbidity of patients, and the 1 year survival rate among these patients remains less than 20%. However, the pathological mechanism of brain metastasis is as yet poorly understood. In this report, we found that metastatic breast tumour cells in the brain highly expressed IL-1β which then ‘activated’ surrounding astrocytes. This activation significantly augmented the expression of JAG1 in the astrocytes, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 46 publications
3
123
0
Order By: Relevance
“…It is worth noting that Jagged1 is also assumed to play a role in tumor development when it is present in the normal cells of the tumor microenvironment (18 ). Our present study has shown that Jagged1 expression in tumor stroma cells is correlated with the presence of the proliferation marker Ki-67 in tumor cells.…”
Section: Discussionsupporting
confidence: 62%
“…It is worth noting that Jagged1 is also assumed to play a role in tumor development when it is present in the normal cells of the tumor microenvironment (18 ). Our present study has shown that Jagged1 expression in tumor stroma cells is correlated with the presence of the proliferation marker Ki-67 in tumor cells.…”
Section: Discussionsupporting
confidence: 62%
“…Tumorinitiating cells that reach the distant organs need to reprogram stromal cells in the microenvironment to build their niche for proliferation (36). Brain is abundant in astrocytes, and we have previously reported that astrocytes can be activated by metastatic cells to support their growth (33). In this study we have shown that prostaglandin can activate astrocytes to release CCL7, which in turn promotes self-renewal of tumor initiating cells.…”
Section: Breast Cancer Mmp1mentioning
confidence: 62%
“…Activation of the Notch pathway in vascular endothelial cells is triggered by norepinephrine-induced Jagged 1 expression in breast cancer cells Accumulating evidence indicates that tumor cell-stromal cell interaction may be influenced by the Jagged/Notch pathway (Zeng et al 2005, Sethi et al 2011, Lu et al 2013, Xing et al 2013, Zender et al 2013. Results from recent studies have indicated that the Notch signaling pathway is directly involved in physiological and pathological angiogenesis (Dufraine et al 2008, Benedito et al 2009).…”
Section: Resultsmentioning
confidence: 99%